Influence of different acid etchings on the superficial characteristics of Ti sandblasted with Al2O3 - Bruno Ramos Chrcanovic; Nathalia Lorrayne Costa Leão; Maximiliano Delany Martins (Materials Research, 2013)
Some implant manufactures use Al2O3 instead TiO2 powder to sandblast the machined dental implant, because Al2O3 powder is commercially more easily available and is cheaper than TiO2 powder. However, Al2O3 powder usually leaves aluminum oxide contamination on the surface, which is potentially toxic. In this work, we subjected Ti discs previously sandblasted with Al2O3 powder to 5 different acid etchings in order to verify which treatment is able to remove incorporated particles of Al2O3 from the surface. One group of samples were only sandblasted and served as control. The samples were analyzed by electron microscopy (SEM, EDS), scanning probe microscopy, and grazing incidence XRD. The control group showed presence of Al2O3 on the surface. Three acid etchings were efficient in removing the alumina from the tested samples. Almost all the tested samples showed higher roughness parameters values than the control samples. Titanium hydride was found in almost all test groups. Moreover, the results suggest that there is no incorporation of the whole Al2O3 particle into the titanium surface after the collision, conversely a particle fragmentation occurs and what remains on the titanium surface are Al2O3 residues.